The Olympic Actors Engagement on Facebook and Twitter during the Buenos Aires Youth Olympic Games - Ρέρρης, Κωνσταντίνος (Πανεπιστήμιο Πελοποννήσου, 2019)
The purpose of the present study is to present the results that has been gained thought data analysis research in the area of social media and sports. It aims to investigate the importance of the social media in sports and especially during the competition days of the Buenos Aires Youth Olympic Games. It aims at investigating the degree of engagement of the Olympic actors through their social media accounts in Facebook and Twitter. The study also aims to investigate the communication philosophy of the actors. An overview of the existing bibliography on the field of social media, social media as a network, social media and Olympic Games, social media and Youth Olympic Games was undertaken. Afterwards the study was carried out through data analysis after collecting data from the Facebook and Twitter accounts of the Olympic actors through the programs Netvizz and TCAT respectively, and further processing to graphs and table through excel and Gephy. The results indicated high levels of engagement between the official accounts of the Olympic actors that were involved in the Buenos Aires Youth Olympic Games. The interrelated with each other creating content that reached high levels of engagement, by forming a wider network that reached greater audiences. The different policies that were implemented varied between the Olympic actor’s official accounts, this created an even more reach and interesting result in the content that was published with the reaction of the audience been the ultimate goal for all the accounts in all the social media platforms. Despite their differences and similarities in the policies they applied and the contents they created, they all contribute by carrying out the images and the action of the games through the social media platforms and engaging viewers from all around the word.
Keywords: Youth Olympic Games - Buenos Aires, Argentina; Mass media and sports; Social media and sports; Ολυμπιακοί Αγώνες Νέων - Μπουένος Άιρες, Αργεντινή; Μέσα μαζικής ενημέρωσης και αθλητισμός; Μέσα κοινωνικής δικτύωσης και αθλητισμός; Engagement; Social media; Interrelation; Youth Olympic Games; Facebook; Twitter